Prophets beyond activism: rethinking the prophetic roots of social justice - O'Brien, Julia M. (Westminster John Knox Press, 2024)
"Challenges the common progressive narrative that the prophets of ancient Israel were primarily concerned with social justice, instead daringly offering more life-giving ways of engaging the prophetic books for the causes of justice"--